2005
DOI: 10.1021/jm050049l
|View full text |Cite
|
Sign up to set email alerts
|

Quinic Acid Derivatives as Sialyl Lewisx-Mimicking Selectin Inhibitors:  Design, Synthesis, and Crystal Structure in Complex with E-Selectin

Abstract: A search for noncarbohydrate sLe(x) mimics led to the development of quinic acid derivatives as selectin inhibitors. At Wyeth we solved the first cocrystal structure of a small molecule, quinic acid, with E-selectin. In the cocomplex two hydroxyls of quinic acid mimic the calcium-bound fucose of the tetrasaccharide sLe(x). The X-ray structure, together with structure based computational methods, was used to design quinic acid based libraries that were synthesized and evaluated for their ability to block the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 25 publications
(38 reference statements)
4
59
1
Order By: Relevance
“…67,68 These same authors showed that the presence of a carboxylic acid functional group was necessary for interaction with the selectins. 67,68 A seriels of QA amides will be prepared, then go to biological screening against our NF-κB activity HTS System. QA amide leads will form a new template for anti-inflammatory agents.…”
Section: Synthesis Of Qa Amide Analogsmentioning
confidence: 99%
See 4 more Smart Citations
“…67,68 These same authors showed that the presence of a carboxylic acid functional group was necessary for interaction with the selectins. 67,68 A seriels of QA amides will be prepared, then go to biological screening against our NF-κB activity HTS System. QA amide leads will form a new template for anti-inflammatory agents.…”
Section: Synthesis Of Qa Amide Analogsmentioning
confidence: 99%
“…See Figure 1-3 from Vink et al 66 Recent work has demonstrated an interaction of QA derivatives with the carbohydrate binding proteins (lectins) involved in key leukocyte-endothelial cell interactions. 67,68 Tetrasaccharide sialyl Lewis x (sLex) ligands found on leukocytes contain sialic acid, L-fucose, and galactose which are essential for calcium-mediated binding of sLex to the carbohydrate binding proteins E, P, and L-selectin. Tetrasaccharide sLex exhibits a poor pharmacokinetic profile and thus cannot be developed as a selectin inhibitor.…”
Section: Biological Activities Of Qa and Its Derivativesmentioning
confidence: 99%
See 3 more Smart Citations